Synthesis of new anilinoquinazoline derivatives as potential anticancer agents: Antiproliferative activity, molecular docking and molecular dynamics studies / Muhammad Kumayl Abdul Wahab - Muhammad Kumayl , Abdul Wahab (2021)
Current reversible epidermal growth factor (EGFR) tyrosine kinase inhibitors of the non-small cell lung cancer (NSCLC) have been resisted by T790M mutation, while irreversible inhibitors introduced to overcome the mutation have faced resistance from C797S mutation. In the effort to discover potential reversible EGFR inhibitors, two series of anilinoquinazoline derivatives were synthesized and characterized, studied for their in vitro antiproliferative activity against NSCLC cell lines, namely A549, H1650 and H1975, and studied for the plausible binding mode in epidermal growth factor receptor kinases with different mutations through molecular docking. In the first series, the anilinoquinazoline scaffold was derivatized through the addition of amide group at the 2nd carbon of the aniline ring. Seven derivatives were synthesized and characterized through 1H NMR, 13C NMR, and HREIMS. Compound 3.7 exhibited the highest activity against all three cell lines, with the IC50 values of 24.60 ± 0.75 μM in A549, 14.83 ± 0.54 μM in H1650, and 21.72 ± 1.21 μM in H1975. The molecular docking study of compound 3.7 indicated that the compound formed the hydrogen bonding with MET793 and ASP855 in wild-type EGFR kinase (WT-EGFR) and MET793 in L858R+T790M mutated EGFR kinase (LRTM-EGFR). In the second series, the anilinoquinazoline scaffold was further derivatized, by extending the chain next to the amide group to include an aromatic ring. Seven derivatives were synthesized and characterized in the series. Compound 3.18 exhibited the significantly highest activity against A549 cell line (IC50: 17.60 ± 1.70 μM), surpassing compound 3.7 (IC50: 24.60 ± 0.75 μM) and the standard drug, gefitinib (IC50: 34.32 ± 1.30 μM), while compound 3.20 exhibited the significantly highest activity against H1975 cell line (IC50: 9.75 ± 1.06 μM), surpassing compound 3.7 (IC50: 21.72 ± 1.21 μM) and gefitinib (IC50: 31.12 ± 0.38 μM). The molecular docking of compound 3.18 in WT-EGFR and compound 3.20 in LRTM-EGFR showed that for both compounds, hydrogen bonding with MET793 and π-π interaction with PHE723 were observed, while the molecular dynamic simulations showed that hydrogen bonding with ASP855 was observed during the simulations of the compounds in the respective EGFR kinases.